Comprative Analysis of Income Tax Article 21 and Article 22 in the Indonesian Tax System: Implication for Compliance and State Revenue - Afsha Harnia; Aisyah Nurhaliza Arifin; Nuratikah Nasution; Samaria Simangunsong; Silva Nurul Hasanah; Galih Supraja6 (CV. AFDIFAL MAJU BERKAH, 2025)
This research aims to comparatively analyze Income Tax Article (PPh) 21 and Income Tax Article (PPh) 22 within the Indonesian taxation system, and examine their implications for taxpayer compliance and state revenue. PPh Article 21 is a tax on income related to employment, services, or activities received by individual domestic taxpayers, such as salaries, wages, honoraria, allowances, and other payments in any name and form. Meanwhile, PPh Article 22 is a tax levied by certain parties related to the import of goods, the purchase of goods by government treasurers, or the sale of goods by certain industries. The research method employed is a literature review and comparative analysis of applicable tax regulations, taxpayer compliance data, and tax revenue data. The findings indicate that differences in object characteristics, collection mechanisms, and tax rates between PPh Article 21 and PPh Article 22 lead to varied implications. PPh Article 21, with its deduction by employers, tends to have a higher level of compliance due to the withholding tax mechanism which reduces the potential for tax evasion. However, regulatory and calculation complexities can affect taxpayer understanding and compliance. On the other hand, PPh Article 22, which functions as a control and revenue security instrument for certain transactions, plays a strategic role in maintaining fiscal stability. Nevertheless, challenges may arise such as potential economic distortions or administrative burdens for certain business actors. The implications for state revenue show that both types of PPh contribute significantly, albeit with different patterns and challenges. This study recommends policy alignment and increased public awareness to optimize taxpayer compliance and the effectiveness of state revenue collection from both types of taxes